Strategi Mengajar Guru di TK Nurul Azmi Sesuai dengan Ajaran Nabi Muhammad - Muhammad Basri; Putri Salsabila; Wirda Hayani Syahputri; Nasrotun Najiha (Departement of Mathematics Education, 2023)
The Prophet Muhammad is the guidance of Muslims, he is the lover of Allah SWT and the last prophet who received revelation in the form of the Koran where we can practice the miracles of the prophet Muhammad until now. When the prophet Muhammad SAW is still alive, he is very excited to broadcast the teachings of Allah SWT, even though there were many insults, insults, and human actions at that time that were not good. But with his steadfastness he did not repay the actions of those who insulted him. The Prophet Muhammad taught his knowledge in the mosques where he moved from one place to another, the method used by the Prophet Muhammad was the method of telling stories, and practicing his knowledge, and setting an example for the people. At Nurul Azmi Kindergarten, they have implemented the teachings of the prophet Muhammad SAW, the teachers in the kindergarten are very enthusiastic about teaching their students to follow the example and practice the teachings of the prophet Muhammad in every child's day. The goal is for children to grow and develop according to the teachings of the Prophet Muhammad